Epithelial to mesenchymal transition and eepithelialisation in wound healing: a review of comparison - Abid Nordin,; Shiplu Roy Chowdhury,; Aminuddin Saim,; Ruszymah Hj Idrus, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Skin wound healing is a complex physiological event, involving many cellular and molecular components. The event of wound healing is the coordinated overlap of a number of distinct phases, namely haemostasis, inflammatory, proliferative and remodelling. The molecular events surrounding wound healing, particularly the reepithelialisation, has been reported to be similar to the epithelial to mesenchymal transition (EMT). In this review, the mechanism between epithelialisation and EMT were compared. Both are characterised by the loss of epithelial integrity and increased motility. In terms of the signalling kinases, Smad and mitogen-activated protein kinase (MAPK) has been reported to be involved in both reepithelialisation and EMT. At the transcriptional level, SLUG transcription factor has been reported to be important for both reepithelialisation and EMT. Extracellular matrix proteins that have been associated with both events are collagen and laminin. Lastly, both events required the interplay between matrix metalloproteinases (MMPs) and its inhibitor. As a conclusion, both reepithelialisation and EMT shares similar signaling cascade and transcriptional regulation to exhibit decreased epithelial traits and increased motility in keratinocytes.